Cognitive Outcome After Islet Transplantation - Aurélie Mailliez, MD; Camille Ternynck, PhD; Arnaud Jannin, MD; Madleen Lemaître, MD; Benjamin Chevalier, MD; Kristell Le Mapihan, MD; Frédérique Defrance, MD; Marie-Anne Mackowiak, MD; Adeline Rollin, MD; Maanaoui Mehdi, MD; Mikael Chetboun, MD; François Pattou, MD, PhD; et al. (Transplantation Direct, 2023)
Background. Severe or repeated hypoglycemia events may favor memory complaints in type 1 diabetes (T1D). Pancreatic islet transplantation (IT) is an alternative option to exogenous insulin therapy in case of labile T1D, implying a maintenance immunosuppression regimen based on sirolimus or mycophenolate, associated with tacrolimus, that may also have neurological toxicity. The objective of this study was to compare a cognitive rating scale Mini-Mental State Examination (MMSE) between T1D patients with or without IT and to identify parameters influencing MMSE. Methods. This retrospective cross-sectional study compared MMSE and cognitive function tests between islet-transplanted T1D patients and nontransplanted T1D controls who were transplant candidates. Patients were excluded if they refused. Results. Forty-three T1D patients were included: 9 T1D patients before IT and 34 islet-transplanted patients (14 treated with mycophenolate and 20 treated with sirolimus). Neither MMSE score (P = 0.70) nor higher cognitive function differed between islet versus non–islet-transplanted patients, whatever the type of immunosuppression. In the whole population (N = 43), MMSE score was negatively correlated to glycated hemoglobin (r = –0.30; P = 0.048) and the time spent in hypoglycemia on the continuous glucose monitoring (r = –0.32; P = 0.041). MMSE score was not correlated to fasting C-peptide level, time spent in hyperglycemia, average blood glucose, time under immunosuppression, duration of diabetes, or beta-score (success score of IT). Conclusions. This first study evaluating cognitive disorders in islet-transplanted T1D patients argues for the importance of glucose balance on cognitive function rather than of immunosuppressive treatment, with a favorable effect of glucose balance improvement on MMSE score after IT.